Gateways to the global economy - Andersson, Åke E.; Andersson, David E. (Cheltenham [England] ; Northampton, MA : E. Elgar, 2000)
A study of international gateway regions. It includes discussions of infrastructure networks such as the Internet and air transport, as well as networking activities such as long-distance scientific co-operation, financial networks and direct investments.
Includes bibliographical references and index.
rpm 24/08/16
Loans
Keywords: Regional economics; Urban economics; Computer networks; Communication and traffic